Gendered challenges of bargaining in agricultural value chain in the Eastern Gangetic Plains - Das, Dipika (University of Southern Queensland, 2019)
Presented by Dipika Das (University of Southern Queensland), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.